2023
DOI: 10.3389/fmicb.2023.1284321
|View full text |Cite
|
Sign up to set email alerts
|

Combined contribution of biochar and introduced AM fungi on lead stability and microbial community in polluted agricultural soil

Xuedong Chen,
Lin Tang,
Kongyang Wu
et al.

Abstract: IntroductionLead (Pb) pollution in agricultural soil has been accelerated by industrial development and human activities, and poses a major threat to agricultural ecosystems. Both biochar and arbuscular mycorrhiza (AM) fungi are considered to play an important role in remediation of Pb contaminated soil.MethodsThe combined remediation effects of introduced AM fungi and biochar on soil properties, Pb availability, microbial community and functional profiles were systematically investigated in unsterilized Pb-po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…The consumption of 1% biochar (mass fraction) resulted in a 72.0% reduction in the amount of soil Cd under accessible conditions according to Wu’s findings [ 41 ]. Chen [ 42 ] demonstrated that including 3% of biochar (mass fraction) resulted in a substantial decrease in the soil Pb concentration. The use of 1% biochar (mass fraction) in this study resulted in reductions of 21.0% and 23.8% in the concentrations of Cd and Pb, respectively, in the rhizosphere soil of Yingshanhong .…”
Section: Discussionmentioning
confidence: 99%
“…The consumption of 1% biochar (mass fraction) resulted in a 72.0% reduction in the amount of soil Cd under accessible conditions according to Wu’s findings [ 41 ]. Chen [ 42 ] demonstrated that including 3% of biochar (mass fraction) resulted in a substantial decrease in the soil Pb concentration. The use of 1% biochar (mass fraction) in this study resulted in reductions of 21.0% and 23.8% in the concentrations of Cd and Pb, respectively, in the rhizosphere soil of Yingshanhong .…”
Section: Discussionmentioning
confidence: 99%